Decrease of Serum AST, ALT, and GGT among Male Alcohol Drinkers with Coffee Consumption Habit. - Tahsin, Yaldis Hassan; Tahsin, Yaldis Hassan; Abdul Hussein, Hussein Kadhem; Ismzel, Thaker waadallah (Journal of the Faculty of Medicine Baghdad, 2005)
Summary:Background: Alcohol is the most important causes of liver cirrhosis. Many of the factors underlying the development of alcoholic liver diseases remain unknown. Recently, some epidemiological studies showed beneficial effects of coffee against the occurrence of alcoholic liver cirrhosis and upon serum liver enzymes level. These observations have been examined in this work.Patients and Methods: The relation of coffee drinking to serum GGT, AST and ALT activities were examined in 59 alcoholic male patients with or without habit of coffee consumption. 35 (59.3%) out of 59 patients were alcoholic drinkers without coffee consumption habit, and 24(40.7%) were alcohol drinkers with coffee consumption. In addition to 24 healthy persons as a control group.Results: Highly significant decrease in GGT (p